Avaliação de um novo tipo de aparelho intraoral para o tratamento de casos graves de síndrome de apneia obstrutiva do sono: s´´erie de casos (Arquivos em Odontologia, 2023)
Aim: This study aimed to evaluate the respiratory parameters among patients diagnosed with severe obstructive sleep apnea (OSA) syndrome treated with a novel design of an oral appliance (OA): a lingual orthosis. Methods: A case series study was conducted with 11 patients suffering from severe OSA, apnea-hypopnea index (AHI) > 30 events/h. All patients underwent pre- and post-treatment overnight polysomnography and were diagnosed by a physician based on polysomnography indexes. All selected patients had a history of nonadherence to continuous positive airway pressure devices. Results: Before treatment, the mean AHI of the sample was 65.9 ± 30.5. After reaching the optimal OA titration, the polysomnography (PSG) showed an average AHI of 10.1 ± 5.5 (p